The long-term mental health benefits of exercise training for physical education students: a comprehensive review of neurobiological, psychological, and social effects - Ma, Yuxin; Mumtaz, Somna (Frontiers in Psychiatry, 2025)
This systematic review examines the long-term effects of exercise training interventions on the mental health of physical education (PE) students, integrating neurobiological, psychological, cognitive, and social perspectives. Evidence indicates that structured exercise programs, including aerobic training, resistance exercise, and mindfulness-based practices, enhance mental well-being through multiple pathways. Aerobic activity elevates brain-derived neurotrophic factor (BDNF) and serotonin, improving mood and stress resilience, while resistance training fosters self-efficacy and emotional regulation. Team sports and group-based interventions mitigate social isolation by strengthening peer bonds, a critical factor in preventing depression and anxiety. Cognitive benefits, such as enhanced memory and academic performance, are linked to exercise-induced neurogenesis and increased cerebral blood flow. However, gaps persist in longitudinal research (>5 years), standardized protocols, and cultural adaptations. Practical recommendations for universities and coaches include integrating mental health monitoring, balancing training intensity to prevent burnout, incorporating mindfulness practices, and promoting peer support networks. By adopting a holistic approach that combines physiological and psychosocial strategies, PE programs can optimize both mental health and academic outcomes. This synthesis underscores the need for evidence-based, multimodal interventions tailored to the unique demands of student-athletes, ultimately supporting their development as high-performing and psychologically resilient individuals.